2018
DOI: 10.1016/j.jcf.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

FAM13A is a modifier gene of cystic fibrosis lung phenotype regulating rhoa activity, actin cytoskeleton dynamics and epithelial-mesenchymal transition

Abstract: Our data show that FAM13A is a modifier gene of CF lung phenotype regulating RhoA activity, actin cytoskeleton dynamics and epithelial-mesenchymal transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 47 publications
3
45
0
Order By: Relevance
“…Fam13a expression was remarkably reduced in the lungs of wild-type (WT) mice exposed to chronic hypoxia comparing to that in the lungs of control mice (Figs 1A and B). It has been reported that FAM13A is expressed in airway cells including mucosal cells, Club cells, and alveolar cells [8, 10]; however it remained unknown whether FAM13A is expressed in the lung vasculature as well. We have generated mice with target deletion of FAM13A ( Fam13a -/- ) in which LacZ cassette was inserted into the intron of the Fam13a gene locus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fam13a expression was remarkably reduced in the lungs of wild-type (WT) mice exposed to chronic hypoxia comparing to that in the lungs of control mice (Figs 1A and B). It has been reported that FAM13A is expressed in airway cells including mucosal cells, Club cells, and alveolar cells [8, 10]; however it remained unknown whether FAM13A is expressed in the lung vasculature as well. We have generated mice with target deletion of FAM13A ( Fam13a -/- ) in which LacZ cassette was inserted into the intron of the Fam13a gene locus.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, FAM13A has been involved in multiple biological processes such as epithelial cell regeneration, tumor cell proliferation and survival, and insulin signaling. FAM13A is known to harbor a Ras-homologous GTPase-activating protein (RhoGAP) domain that is important for proliferation and survival in lung adenocarcinoma cell A549 [24], and this domain could activates RhoA which can affect actin cytoskeleton and promotes epithelial-to-mesenchymal transition in cystic fibrosis lung [8]. FAM13A also has two coiled-coil domains that often play a role in the protein-protein interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fam13a expression was remarkably reduced in the lungs of wild-type (WT) mice exposed to chronic hypoxia comparing to that in the lungs of control mice under normoxic condition (Fig 1A and 1B). It has been reported that FAM13A is expressed in airway cells including mucosal cells, Club cells, and alveolar cells [8,10]; however it remained unknown whether FAM13A is expressed in the lung vasculature as well. We have generated mice with target deletion of FAM13A (Fam13a -/-) in which LacZ cassette was inserted into the intron of the Fam13a gene locus.…”
Section: Fam13a Is Expressed In Lung Vasculaturesmentioning
confidence: 99%
“…Recent genome-wide association studies identified family with sequence similarity 13, member A (FAM13A) gene as a genetic locus associated with pulmonary function [4], and it is known to be associated with lung diseases including chronic obstructive pulmonary disease (COPD) [5], asthma [6] and pulmonary fibrosis [7][8][9]. Moreover, causative role of FAM13A in the development of COPD has been revealed.…”
Section: Introductionmentioning
confidence: 99%